Nonrestorative Caries Treatment: A Systematic Review Update - María Belén Cabalén; Gustavo Fabián Molina; Alejandra Bono; Michael F. Burrow (Elsevier, 2022)
Caries is the most prevalent chronic noncommunicable disease. Strategies to prevent its onset and early interventions to arrest the progression of early lesions have been emphasised throughout recent decades to avoid or delay the restorative spiral of the tooth. More individuals are retaining their natural teeth into old age, thereby necessitating ongoing restorative dentistry intervention for their maintenance. The aim of this systematic review was to update the state of the art regarding clinical studies reporting the effectiveness of different nonrestorative caries treatment options in the 5-year period from 2017 to 2022. Relevant articles were retrieved from 2 electronic databases, including randomised clinical trials (RCTs) published from January 2017 until April 2022, assessing effectiveness and secondary effects of at least one nonrestorative caries treatment option, carried out with adults and/or children with noncavitated or cavitated carious lesions on either primary or permanent teeth and diagnosed by radiographs or visual/tactile assessment. All 35 included articles presented the results of RCTs with a follow-up period ranging from 6 to 84 months. Most of these studies were considered high-quality articles with a low risk of bias. Sealants and fluoride gels and varnishes were mentioned in 12 studies as effective strategies to prevent the onset of caries lesions and to arrest them in the early stages. Resin infiltration reported high caries arresting rates in noncavitated proximal lesions in 10 publications. Silver diammine fluoride presented high caries-arresting rates in open dentin lesions, both in primary and permanent dentitions as well as in root caries lesions that were accessible for cleansing. New evidence has been published between 2017 and 2022 as the result of numerous clinical studies providing further evidence of the effectiveness of nonrestorative caries treatment options.